2017
DOI: 10.1097/grf.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

In Search for the Best Minimally Invasive Hysterectomy Approach for the Large Uterus: A Review

Abstract: Review of literature is conducted to determine the best minimally invasive hysterectomy (MIH) route for large uterus, identify preoperative considerations and describe alternative techniques to power morcellation. Studies after 2010 revealed multiple MIH approaches. Vaginal hysterectomy is preferred over laparoscopic and laparoscopic assistance with less operative time and hospital cost. In morbidly obese patients with large uteri, total laparoscopic hysterectomy is superior to vaginal hysterectomy with lesser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…However, laparoscopic hysterectomy (LH) evolves continuously, and concomitant salpingectomy and adhesiolysis after previous cesarean may be easier to perform laparoscopically, and the feasibility of VH decreases with increasing body mass index and uterus size [2]. LH is recommended over abdominal hysterectomy (AH), but when it comes to larger uteri, the best minimally invasive approach is still debated [3]. The removal of larger uteri through small laparoscopic incisions involves morcellation, which became controversial as cases with occult leiomyosarcoma emerged [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, laparoscopic hysterectomy (LH) evolves continuously, and concomitant salpingectomy and adhesiolysis after previous cesarean may be easier to perform laparoscopically, and the feasibility of VH decreases with increasing body mass index and uterus size [2]. LH is recommended over abdominal hysterectomy (AH), but when it comes to larger uteri, the best minimally invasive approach is still debated [3]. The removal of larger uteri through small laparoscopic incisions involves morcellation, which became controversial as cases with occult leiomyosarcoma emerged [3].…”
mentioning
confidence: 99%
“…LH is recommended over abdominal hysterectomy (AH), but when it comes to larger uteri, the best minimally invasive approach is still debated [3]. The removal of larger uteri through small laparoscopic incisions involves morcellation, which became controversial as cases with occult leiomyosarcoma emerged [3]. After a warning from the United States Food and Drug Administration in 2014 against power morcellation, complications increased as AH was used instead of LH [4].…”
mentioning
confidence: 99%
“…Existing studies evaluating hysterectomy outcomes in large uteri do not consider the location and relationship to the vascular pedicles. 5 Our analysis highlights the impact of these contributing factors on surgical outcomes. Compared with the other uterine types, the Type 1 uterus, approached using the standard TLH technique, was associated with less blood loss, shorter operative time, fewer complications, and fewer conversions to open surgery.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, vaginal vault suture, uterine myomectomy, and LESS hysterectomy for increased uterine weight are considered challenging. In 2017, a review article suggested that minimally invasive hysterectomy for the large uterus is feasible [23]. However, only two RCTs comparing LESS and MLS were included in the analysis; moreover, women with uterine size greater than 18 weeks were excluded.…”
Section: Less In Benign Uterine Diseasesmentioning
confidence: 99%